Environmental management concepts, principles, and practices with introduction to Philippine EIS system - Mendoza, Ernesto H.; Garcia, Lorma S.P (Unlimited Books Library Services and Publishing, 2018)
Many have considered Environmental Management as an important instrument in spearheading the demands and clamor to find different ways to help save the world. It is a branch of learning that deals with the application of advanced analytical methods to facilitate better judgments in making choices affecting the environment.